Crystal Engineering of Ibuprofen and Caffeine by Cocrystal Formation Using Solvent Evaporation and Slurry Methods - Mikhania Christiningtyas Eryani; Yudi Wicaksono; Budipratiwi Wisudyaningsih; Kuni Barikah; Hery Febrianto (Fakultas Farmasi Universitas Andalas, 2026)
Ibuprofen is a pharmaceutical active compound used to treat mild to moderate pain and fever. However, ibuprofen has low solubility in water. One method to increase solubility is cocrystal formation. The ibuprofen cocrystal was prepared in this study using caffeine as a coformer at a 1:1 molar ratio via solvent evaporation and slurry methods. The results of the XRD and thermal analysis of the sample indicate that a new solid phase is formed in the specific sa mple, which is different from both of its constituent components. Morphologically, the resulting cocrystals show a change in shape from their constituent compounds as well as a change in size. The solubility test results show that cocrystal formation is able to increase the solubility of ibuprofen. The conclusion of this study is that ibuprofen cocrystals can be formed with the coformer caffeine at a molar ratio of 1:1 using the slurry method and solvent evaporation.